The Effectiveness of Stunting Education Using Leaflet Media to Increase the Knowledge of Women of Childbearing Age in the Sungai Tabuk 1 Health Center Work Area (HEALTH CARE: JURNAL KESEHATAN, 2024)
AbstractBackground: Stunting is a condition where a child experiences growth disorders, which causes height to be not in accordance with their age. One of the factors that can influence the incidence of stunting is the mother's knowledge. Knowledge about stunting is very necessary for a mother because the mother's lack of knowledge about stunting can cause children to be at risk of stunting. One way to increase parental knowledge is by providing health education. Objective: to determine the effectiveness of providing education about stunting using leaflet media for women of childbearing age in the Sungai Tabuk 1 Health Center Working Area.Method: The method used in this study was a pre-experimental study with a one-group pretest-posttest design by involving one group of subjects who were observed before the intervention, then observed again after the intervention. Sampling in this study used the Accidental Sampling method with 15 respondents. Data analysis used the Wilcoxon test.Results: The results of the study showed that the distribution of the majority of respondents' ages was 21-35 years (53.3%). The majority of respondents' education level was at the high school level (53.4%) and some respondents were unemployed (80%). Before being given education, the level of knowledge of respondents was in the good category (53.4%) in the sufficient category (40%) and the less category (6.6%). The level of knowledge of respondents after being given education about stunting was in the good category (86.6%) in the sufficient category (13.4%). The Wilcoxon statistical test showed that the p-value was 0.001, which means that there was a significant increase in knowledge before and after stunting education using leaflet media.Conclusion: Providing stunting education using leaflet media is effective in increasing the knowledge of women of childbearing age in the Sungai Tabuk 1 work areaKeywords: Age, Occupation, Education, Effectiveness, Knowledge